Sobre o método genealógico de Foucault a partir da genealogia nietzschiana - Rossi, Pablo Ruiz Andrade (2022)
The present dissertation aims to present Foucault's genealogical perspective, based on his writings about Nietzsche's genealogical stance. Having as main support point Foucault's text: Nietzsche, genealogy and history. The work consists, in a first moment, in observing the problematizations made by the French philosopher in parts I, II, III and IV of the text in question. In this way, we will analyze how Foucault problematizes the use of various German words that refer to a notion of origin on the part of Nietzsche and their implications for genealogical work. In the second moment, parts V, VI and VII will be analyzed. In which Foucault discusses the relation of genealogy with history, based on the three uses of historical knowledge proposed by Nietzsche in the Second Extemporaneous Consideration.